(untitled) (Third Sector Social Economic Review, 2017)
The prior condition of a research beingscientific is that is measurable. The main purpose of this article is to investigate the scales used in marketing articles in some journals (2017-2017) that are chosen by considering this term. In addition, findings from this study were compared with a similar study published between 2002 and 2005 and developments are evaluated.